المسرح المدرسي بين المفهوم والفن والتقنية - عمر, يوسف (University of El-oued, 2020)
يعتبر مسرح الأطفال المدرسي من أبرز الأدوات الفنّية في تنشئة الطّفولة ومن أهمّ وسائل التّربية على القيم الأصيلة والمبادئ الإسلامية النّبيلة، ومن أرقى وسائط الثّقافة للمعرفة والاستكشاف، وتنمية الإبداع؛ أجلَ مدّ الطّفل حقّه من الثّقافة، وبناء شخصيته وإعداده للمستقبل، على اعتبار أنّه الطّاقة البشرية الأساسية في المجتمع. والمسرح المدرسي يشارك فنون أدب الطفل في مفهومها وأهدافها، ويفارقها في كثير من الجوانب التعليمية والتّقنية، فما مفهوم المسرح المدرسي؟ وماهي عناصره الفنية؟ وماهي مواصفات تقنيات؟ ذلك ما سنحاول بسطه في هذه المقالة، بالاعتماد على المنهج الوصفي التحليلي. The school theater is one of the most important artistic tools in the upbringing of childhood and among the most important means of education for the original values and noble Islamic principles, and of the finest means of culture for knowledge and exploration, and the development of creativity; the development of the child's right to culture; and the building and preparation of his personality for the future, as the basic human energy of society. The school theater shares the arts of children's literature in their concept and objectives, and it is very much a difference in educational and technical aspects, what is the concept of the school theater? What are its technical elements? What are the specifications of technologies? That's what we'll try to simplify in this article, depending on the descriptive analytical approach.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج03. ع.02. جامعة الوادي
Keywords: مسرح مدرسي؛ طفل؛ بنية فنية، تمثيل; School Theater; Child; Art Architecture; representation